Patterns of resources devoted to research and experimental development in the OECD area, 1963-1971 - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 1975)
Chapter One of this report deals with trends in total R&D (Research and development) expenditures and total R&D manpower during the period. Chapter Two discusses the role of the various sectors of the economy in the funding and performance of national R&D efforts. Chapter Three deals with two separate topics, first the breakdown of national R&D efforts by type of activity (basic research, applied research and experimental development) and second trends in the types of inputs into R&D. The body of the text thus deals with changes in the level and pattern of Member countries "science potentials" between 1963 and 1971.
ne 4/04/2018
Loans
Keywords: Research; Industrial